Tergoceracris, a new genus and six new species of montane grasshoppers (Orthoptera: Acrididae: Ommatolampinae) from Dominican Republic and Puerto Rico - Perez-Gelabert, Daniel E.; Otte, Daniel (Zootaxa, 2003)
The new genus Tergoceracris consists of six new species; all are brachypterous, semi-arboreal and montane grasshoppers. They are distinguished from all other known neotropical acridoids by having exaggerated and vertically projecting furculae in the males. Two new species are from the Dominican Republic (Tergoceracris ocampensis n. sp. and Tergoceracris ebanoverde n. sp.) and four from Puerto Rico (Tergoceracris guajataca n. sp., Tergoceracris cerropunta n. sp., Tergoceracris cayey n. sp., and Tergoceracris luquillensis n. sp.).